Regulation of Peroxisome Proliferator-Activated Receptor Pathway During Torpor in the Garden Dormouse, Eliomys quercinus - Watts, Alexander J.; Logan, Samantha M.; Kübber-Heiss, Anna; Posautz, Annika; Stalder, Gabrielle; Painer, Johanna; Gasch, Kristina; Giroud, Sylvain; Storey, Kenneth B. (Frontiers in Physiology, 2020)
Differential levels of n-6 and n-3 essential polyunsaturated fatty acids (PUFAs) are incorporated into the hibernator’s diet in the fall season preceding prolonged, multi-days bouts of torpor, known as hibernation. Peroxisome proliferator-activated receptor (PPAR) transcriptional activators bind lipids and regulate genes involved in fatty acid transport, beta-oxidation, ketogenesis, and insulin sensitivity; essential processes for survival during torpor. Thus, the DNA-binding activity of PPAR𝛼, PPAR𝛿, PPAR𝛾, as well as the levels of PPAR𝛾 coactivator 1𝛼 (PGC-1𝛼) and L-fatty acid binding protein (L-FABP) were investigated in the hibernating garden dormouse (Eliomys quercinus). We found that dormice were hibernating in a similar way regardless of the n-6/n-3 PUFA diets fed to the animals during the fattening phase prior to hibernation. Further, metabolic rates and body mass loss during hibernation did not differ between dietary groups, despite marked differences in fatty acid profiles observed in white adipose tissue prior and at mid-hibernation. Overall, maintenance of PPAR DNA-binding activity was observed during torpor, and across three n-6/n-3 ratios, suggesting alternate mechanisms for the prioritization of lipid catabolism during torpor. Additionally, while no change was seen in L-FABP, significantly altered levels of PGC-1𝛼 were observed within the white adipose tissue and likely contributes to enhanced lipid metabolism when the diet favors n-6 PUFAs, i.e. high n-6/n-3 ratio, in both the torpid and euthermic state. Altogether, the maintenance of lipid metabolism during torpor makes it likely that consistent activity or levels of the investigated proteins are in aid of this metabolic profile.